THE REPERCUSSIONS OF COVID-19 POST PANDEMIC ON KUNINGAN'S TOURIST DESTINATIONS - AULIA SYIFA SAFIRA; AULIA DANIBRATA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this study is to determine the effect of COVID-19 after effect on Behavioral Intention from tourists towards Kuningan’s tourist destinations. The research design in this thesis uses descriptive research and causality research, measuring each variables using a likert scale of 1-5. This research takes primary and secondary data with data collection, namely through distributing questionnaires through website and on field research. The results of this study indicates that there is an influence on Behavioral Intention from tourists towards Kuningan’s tourists destination during Post Pandemic.